2000
DOI: 10.4049/jimmunol.165.1.548
|View full text |Cite
|
Sign up to set email alerts
|

IFN-β-1b Inhibits IL-12 Production in Peripheral Blood Mononuclear Cells in an IL-10-Dependent Mechanism: Relevance to IFN-β-1b Therapeutic Effects in Multiple Sclerosis

Abstract: IL-12 is a proinflammatory cytokine secreted by dendritic cells in response to microbial Ags and mitogens. IL-12 is thought to contribute to the pathogenesis of autoimmune diseases such as multiple sclerosis (MS). This is based on studies in experimental allergic encephalomyelitis and the demonstration that PBMC IL-12 production correlates with disease progression in MS. IFN-β-1b is an effective treatment for MS, which is thought to involve in part inhibition of proinflammatory cytokines. In this study we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 48 publications
5
50
0
1
Order By: Relevance
“…Correspondingly, IFN-g production by MNCs was significantly reduced by DCs pretreated with IL-10 1 IFN-b . Together with the results by Wang et al [22] that endogenous production of IL-10 is a required cofactor for the IFN-b -1b inhibitory effect on IL-12, the present findings suggest that effects obtained by IFN-b and IL-10 in combination on DCs in vitro could provide a novel mechanism to manipulate DCs in a desirable way in MS.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Correspondingly, IFN-g production by MNCs was significantly reduced by DCs pretreated with IL-10 1 IFN-b . Together with the results by Wang et al [22] that endogenous production of IL-10 is a required cofactor for the IFN-b -1b inhibitory effect on IL-12, the present findings suggest that effects obtained by IFN-b and IL-10 in combination on DCs in vitro could provide a novel mechanism to manipulate DCs in a desirable way in MS.…”
Section: Discussionsupporting
confidence: 84%
“…The concentration of 1000 U/ml of IFN-b is 5±10 fold higher than the concentration achieved in the circulation by current treatment of MS with IFN-b -1b [20]. The concentration of 1000 U/ml has, however, been shown to inhibit IL-12 production by DCs [15] and to modulate functionally important molecules on DCs [21], and is widely used for in vitro studies [22]. DCs from both MS patients and healthy controls showed strong allostimulatory capacity in allogeneic MLR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In virally infected mice, endogenously expressed IFN-␣␤ inhibited the ability of LPS to induce IL-12, while neutralization of IFN-␣␤ enhanced IL-12 and IFN-␥ production (34). Lastly, Wang et al (35) demonstrated that IFN-␤ inhibits IL-12 production in Staphylococcus aureus Cowan-plus IFN-␥-stimulated human PBMC in an IL-10-dependent mechanism. In this study, the authors did not observe enhancement by IFN-␤ of basal IL-10 production in monocytes and suggested that the IFN-␤ effect was mediated by inhibition of IFN-␥ priming.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-β has been shown to decrease clinical and MRI measures of disease activity in MS (Interferon Beta Study Group 1993, Paty et al, 1993,PRISMS 1998,Simon et al, 1999. IFN-β acts to increase IL-10 levels and reduce IL-12 levels in MS patients, thus improving the ratio of IL-10 to IL-12 (Correale et al, 1995,Rudick et al, 1996,Wang et al, 2000,Byrnes et al, 2002, Berghella et al, 2005, Ersoy et al, 2005. The mechanism of IL-12 suppression has been shown to depend on IL-10 induction (Wang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…IFN-β acts to increase IL-10 levels and reduce IL-12 levels in MS patients, thus improving the ratio of IL-10 to IL-12 (Correale et al, 1995,Rudick et al, 1996,Wang et al, 2000,Byrnes et al, 2002, Berghella et al, 2005, Ersoy et al, 2005. The mechanism of IL-12 suppression has been shown to depend on IL-10 induction (Wang et al, 2000). Increased CSF IL-10 levels during IFN-β treatment correlate with clinical response to therapy (Rudick et al, 1998).…”
Section: Introductionmentioning
confidence: 99%